Short-Term Prognostic Efficacy of mGPS and LCS in Patients With Acute Heart Failure - Wang, Jing; Xie, Ling; Lyu, Ping; Zhou, Feng; Cai, Hong-Li; Qi, Rong-Xing; Zhang, Qing (Frontiers in Cardiovascular Medicine, 2022)
Aim: Systemic inflammation plays an important role in the occurrence and development of acute heart failure. The modified Glasgow Prognostic Score (mGPS) and “lymphocyte C-reactive protein score” (LCS) are used to assess the inflammation levels in cancer patients. The purpose of this study was to assess the prognostic value of these two inflammation-related scoring systems in patients with acute heart failure. Methods: 250 patients with acute heart failure were enrolled in this study. The mGPS and LCS scores were recorded after admission. All patients were divided into 2 groups: the death group and the survival group according to the 3-month follow-up results. The predictive values of mGPS and LCS were assessed using receiver-operating characteristic (ROC) analyses. Univariate and multivariate logistic analyses were used to evaluate the relationships between variables and endpoint. Results: The levels of mGPS and LCS in the death group were significantly higher than those in the survival group (P<0.05). The areas under the ROC curve of the mGPS and LCS for predicting death were 0.695 (95%CI: 0.567 0.823) and 0.736 (95%CI: 0.616 0.856), respectively. Multivariate analysis demonstrated that both LCS, LVEF and serum direct bilirubin were independent predictors of all-cause death, excluding mGPS. Conclusions: Compared with mGPS, LCS is independently associated with short-term outcomes in patients with acute heart failure. LCS was a clinically promising and feasible prognostic scoring system for patients with acute heart failure.